2015
DOI: 10.1681/asn.2014070664
|View full text |Cite
|
Sign up to set email alerts
|

Tamm-Horsfall Protein Regulates Granulopoiesis and Systemic Neutrophil Homeostasis

Abstract: Tamm-Horsfall protein (THP) is a glycoprotein uniquely expressed in the kidney. We recently showed an important role for THP in mediating tubular cross-talk in the outer medulla and in suppressing neutrophil infiltration after kidney injury. However, it remains unclear whether THP has a broader role in neutrophil homeostasis. In this study, we show that THP deficiency in mice increases the number of neutrophils, not only in the kidney but also in the circulation and in the liver, through enhanced granulopoiesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
67
1
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(72 citation statements)
references
References 52 publications
1
67
1
3
Order By: Relevance
“…In fact, it was previously observed that mice deficient in THP exhibit a systemic inflammatory phenotype, marked by increased levels of several cytokines and chemokines in the blood (38). We observed recently that THPϪ/Ϫ mice have systemic neutrophilia caused by increased granulopoiesis in the bone marrow (41). This was caused by activation of the IL-23/IL-17 axis in the THPϪ/Ϫ kidneys.…”
Section: Thp-dependent Cross Talk In Neutrophil Homeostasis Beyond Thmentioning
confidence: 82%
See 4 more Smart Citations
“…In fact, it was previously observed that mice deficient in THP exhibit a systemic inflammatory phenotype, marked by increased levels of several cytokines and chemokines in the blood (38). We observed recently that THPϪ/Ϫ mice have systemic neutrophilia caused by increased granulopoiesis in the bone marrow (41). This was caused by activation of the IL-23/IL-17 axis in the THPϪ/Ϫ kidneys.…”
Section: Thp-dependent Cross Talk In Neutrophil Homeostasis Beyond Thmentioning
confidence: 82%
“…4B) (16,18,25,41). The relative THP deficiency, seen in wild-type kidneys, may indeed be part of the pathophysiology of ischemic AKI (27).…”
Section: Thp-dependent Model Of Tubular Cross Talk In Akimentioning
confidence: 99%
See 3 more Smart Citations